Cooperative Learning Through Team Accelerated Instruction in Grade IV Mathematics - Irwanto, Moch; Rindaningsih , Ida (Indonesian Journal of Islamic Studies, 2024)
General Background: Cooperative learning methodologies have gained prominence in educational settings for their potential to enhance student engagement and comprehension. Specific Background: Among these, the Teams Accelerated Instruction (TAI) model has shown promise, particularly in mathematics education, yet its specific impacts in the context of Madrasah Ibtidaiyah remain underexplored. Knowledge Gap: Despite existing literature on cooperative learning, there is a lack of qualitative studies that examine TAI's effectiveness from a phenomenological perspective in Indonesian primary education. Aims: This study aims to investigate the teaching practices of a grade IV mathematics teacher using the TAI method and to assess its effectiveness in promoting learning outcomes. Results: Utilizing qualitative research methods, including observation, in-depth interviews, and documentation, findings indicate that TAI significantly enhances student collaboration and understanding of mathematical concepts, fostering a more interactive classroom environment. Novelty: This research contributes a phenomenological perspective to cooperative learning, highlighting the lived experiences of both teacher and students within the TAI framework. Implications: The insights gained underscore the importance of implementing cooperative learning strategies like TAI in Madrasah Ibtidaiyah, offering practical implications for educators aiming to improve pedagogical practices and student learning outcomes in mathematics. This study provides a foundation for further research into cooperative learning methods within diverse educational contexts. Highlights: Effectiveness of TAI: The Teams Accelerated Instruction method significantly improves student engagement and understanding in mathematics. Phenomenological Approach: The study employs a phenomenological perspective, providing insights into the experiences of teachers and students in cooperative learning settings. Practical Implications: Findings highlight the potential for TAI to enhance pedagogical practices in Madrasah Ibtidaiyah, suggesting a need for broader implementation. Keywords: Teams Accelerated Instruction, cooperative learning, phenomenology, mathematics education, Madrasah Ibtidaiyah.